2003
DOI: 10.1188/03.onf.249-257
|View full text |Cite
|
Sign up to set email alerts
|

Meaning of Illness and Spirituality in Ovarian Cancer Survivors

Abstract: Knowledge of the unique survivorship issues of patients with ovarian cancer can enable nurses to improve their care for these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 15 publications
5
76
1
5
Order By: Relevance
“…However, despite the known burden of symptom clusters, little is known about the experience and meaning of MSs for individuals with advanced cancer. Yet, these have profound implications for patients' physical, psychological and social health [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the known burden of symptom clusters, little is known about the experience and meaning of MSs for individuals with advanced cancer. Yet, these have profound implications for patients' physical, psychological and social health [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Most QOL instruments focus on the effects of diagnosis and initial cancer treatment [2] whereas the specific concerns and needs of long-term survivors are seldom measured. The Quality of Life -Cancer Survivor (QOL-CS) is one of the few instruments that has been designed specifically for the assessment of QOL in long-term cancer survivors and has been validated or used in several American studies [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In Ferrell, Smith, Juarez, and Melancon's (2003) study, fatigue was a problem because it reduced women's ability to continue with their daily responsibilities and they often felt they had insufficient energy to support their families. Donovan and Ward (2005) reported that 27 out of 49 women in their descriptive, correlational study identified fatigue as a distressing and uncontrollable symptom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…because women may be distressed if they do not have enough energy to maintain their usual roles (Ferrell, Smith, Juarez, et al, 2003). Communication about this issue needs to be improved and research efforts need to continue to develop and test interventions to decrease cancer-related fatigue.…”
Section: Referencesmentioning
confidence: 99%